Uang Jujur dalam Adat Lampung Pesisir dalam Perspektif Hukum Ekonomi Syariah - Ferry Antoni (UNES Law Review, 2023)
One form of marriage in the Lampung Pesisir custom is called "perkawinan jujur" or "honest marriage." This type of marriage is conducted by involving "jujur" money (jojokh), which is given by the prospective groom to the family of the prospective bride before the marriage contract (akad nikah). However, during the actual akad nikah ceremony, the jojokh money is not mentioned. In practice, the amount of jojokh money requested by the woman can sometimes be quite high. This paper examines how Islamic law views such a practice by referring to legal reading methods in ushul fiqh and fiqh. The analysis shows that jojokh can be likened to a dowry (mahar) in many aspects. Jojokh also fulfills the conditions of being a valid 'urf (acceptable custom). Regarding the specific amount of jojokh money, Islamic law only sets the minimum limit for the dowry (mahar) that must be given. However, there is no set maximum limit. As long as the amount of jojokh does not burden the prospective groom, any nominal amount of jojokh remains acknowledged and valid in Islamic law. Keywords: Dowry, jojokh, custom marriage, Lampung Pesisir.